2004
DOI: 10.1172/jci22104
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral vessel laminins and IFN-γ define Trypanosoma brucei brucei penetration of the blood-brain barrier

Abstract: Subspecies of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 43 publications
6
89
0
Order By: Relevance
“…Mice and rats show a similar outcome of T. b. brucei infection, and the penetration of parasites into the brain parenchyma occurs between 12 and 22 dpi. 26,27 It was observed that all transcripts for CXCL10, lipocalin 2, and SLPI were differentially upregulated in brains of infected rats at late stage similar to what was observed in mice ( Figure 3A-C ). Because of limitations in commercially available antibodies against rat proteins, only lipocalin 2 was analyzed in rat CSF.…”
Section: Identification Of Genes Differentially Expressed In the Braisupporting
confidence: 64%
See 1 more Smart Citation
“…Mice and rats show a similar outcome of T. b. brucei infection, and the penetration of parasites into the brain parenchyma occurs between 12 and 22 dpi. 26,27 It was observed that all transcripts for CXCL10, lipocalin 2, and SLPI were differentially upregulated in brains of infected rats at late stage similar to what was observed in mice ( Figure 3A-C ). Because of limitations in commercially available antibodies against rat proteins, only lipocalin 2 was analyzed in rat CSF.…”
Section: Identification Of Genes Differentially Expressed In the Braisupporting
confidence: 64%
“…One suggestion from this is that cells may readily cross the blood-CSF barrier, but crossing of the BBB requires more complex mechanisms, which have been in part recently elucidated. 26,29 Thus, there is most likely a delay in gaining access into brain parenchyma compared with CSF, implying that finding trypanosomes combined with mild pleocytosis (< 20 WBC/μL of CSF) in the CSF may not be a reliable parameter for disease staging in African trypanosomiasis. Perhaps, molecules that are released from brain parenchymal cells as a consequence of events taking place behind the BBB is better indicators of late stage infection.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse BBB-crossing models have been crucial in demonstrating the central role of laminin composition of the basement membrane of the microvascular endothelial cells, as well as the role of IFN-g in the migration process of trypanosomes through the BBB [62]. This recent research involved several knockout mice strains, namely IFN-g À/À , IFN-g receptor À/À , p40 subunit of IL-12 À/À (IL-12p40 À/À ) and recombinant activating gene-1 À/À (RAG-1 À/À ).…”
Section: Reviewmentioning
confidence: 99%
“…38 Several studies have demonstrated that the use of subtherapeutic doses of diminazene aceturate may prolong survival of horses experimentally infected by T. brucei spp., but it is associated with subsequent invasion of the central nervous system by trypanosomes and production of necrotizing encephalitis. 14,18,19,26,28,34,39,44 Diminazene aceturate clears trypanosomes from tissues except in the central nervous system, 17 because the drug does not cross the blood-brain barrier (BBB). 19,31 Thus, trypanosomes in the central nervous system survive antitrypanosomal therapy, and with a change in their surface glycoproteins may lead to new parasitemias.…”
Section: Discussionmentioning
confidence: 99%
“…20 It is believed that invasion of the central nervous system by trypanosomes occurs where the BBB has been disrupted, either directly by the parasites or by release of chemical mediators, including cytokines and proteases. 13,23,26 An interaction between the trypanosomes and the host response to them could promote tissue damage and facilitate parasitic entry into the central nervous system. 23 This scenario is supported by the histopathologic changes and immunohistochemistry in the present report.…”
Section: Discussionmentioning
confidence: 99%